Relationship between perception of training outsourcing and organizational commitment among support staff at Naza Talyya Hotel , Melaka / Muhammad Zulfadli Nordin - Nordin, Muhammad Zulfadli (Faculty of Office Management and Technology, 2013)
The human resource practice of training outsourcing is emerging as one of the fastest - growing segments of the broader business process outsourcing industry. In spite of its growing popularity in both academic literature and professional practice, training outsourcing IS continuously subjected to critical reviews and on-going debates regarding the decision to 'outsource' or 'not to outsource'. There exists, however, a paucity of research on training outsourcing as a human resource development (HRD) practice on different organizational outcomes. This dissertation is an exploratory study that attempted to build on and extend previous research that examined the relationship between training and organizational commitment by focusing on outsourced training. This study also fills an important gap in the training outsourcing literature by taking into consideration employee perceptions and preferences towards outsourced training. The study is framed by social exchange theory to explore possible relationships between training outsourcing and organizational commitment.